Responses of economically important crops to crude extracts of cucumis myriocarpus fruit when used as a pre-emergent bio-nematicide - Mafeo, Tieho Paulus (My University, 2012)
High yield losses in various crops due to plant-parasitic nematodes are associated with high initial nematode population densities (Pi). Uses of synthetic nematicides to reduce Pi were dependent on the physiological effect of materials on the protected crops, resulting into the coining of pre-emergent and post-emergent nematicides. Crude extracts of wild cucumber (Cucumis myriocarpus) fruit consistently reduced nematode population densities of the southern root-knot nematode (Meloidogyne incognita) when used as a post-emergent bio-nematicide. The purpose of this study was to investigate the compatibility of crude extracts of C. myriocarpus fruit when used as a pre-emergent bio-nematicide on germination and emergence of commercially important dicotyledonous and monocotyledonous crops using empirical tests and computer-generated models. Studies were conducted over a period of three years to assess the effects of this material on growth of various seedlings. Seven treatments comprising crude extracts of C. myriocarpus fruit (0, 2.5, 5, 7.5, 10, 12.5 and 15 g/pot) and test solutions (0, 25, 50, 75, 100, 125 and 150 g/ℓ distilled water) were used for emergence and germination in initial studies. Generally, 18 days after the treatments, variables measured and levels of crude extracts of C. myriocarpus fruit had negative quadratic relationships, which suggested that they had density-dependent growth responses. Subsequent studies were conducted using three selected crops each from the families Alliaceae, Gramineae and Solanaceae under greenhouse conditions, each with reduced concentration of 10 treatments (0, 0.25, 0.50, 0.75, 1.00, 1.25, 1.50, 1.75, 2.00 and 2.25 g material/pot). Using variables of various organs and crops, significant means were subjected to the Curve-fitting Allelochemical Dosage Response (CARD) computer model, which was characterised by six biological indices, viz. threshold stimulation (Dm), xli saturation level (Rh), 0% inhibition (D0), 50% inhibition (D50), 100% inhibition (D100) and transformation level (k). The model demonstrated that the responses of the three crops from each family when regressed to dosages of crude extracts of C. myriocarpus fruit exhibited the density-dependent growth patterns, characterised by responses that included stimulation, saturation and inhibition. The integrated sensitivities (Σk) of the tested crops to crude extracts of C. myriocarpus fruit ranged from Σk = 9 to Σk = 51, with eggplant (Solanum melongena) and sorghum (Sorghum bicolor) being the most sensitive, while tomato (Solanum lycopersicum) was the least sensitive. Using the data depicting the stimulation range from CARD model, viz. (Dm), which is a threshold stimulation dosage and (Rh), which is a saturation dosage, mean dosage stimulation response (MDSR) was determined for chive (Allium schoenoprasum), leek (Allium ampeloprasum), onion (Allium cepa), maize (Zea mays), millet (Panicum miliaceum), sorghum, eggplant, pepper (Capsicum annum) and tomato as being 1.19, 0.68, 0.45, 1.13, 0.86, 1.12, 0.74, 1.11, and 0.53 g, respectively. These MDSR values are dosages which when applied for respective crops at direct seeding would not affect germination or emergence. MDSR values were validated for onion, millet and tomato, resulting in approximately 100% suppression of nematodes in all three test crops. In contrast, 100% emergence occurred in millet and tomato, while the validated MDSR reduced emergence on onion by 15%, which confirmed the sensitivity of this crop to crude extracts of C. myriocarpus fruit. In conclusion, crude extracts of C. myriocarpus fruit have the potential for use as pre-emergent bio-nematicide in suppression of plant-parasitic nematodes in various crops.
Thesis (Ph.D. Agriculture (Horticulture)) -- University of Limpopo, 2012
Keywords: Cucumis myriocarpus; Bio-nematicide; Cucumbers; Cucumbers -- Diseases and pests.; Cucumbers -- Disease and pest resistance